HTLV-1 in Pregnancy and Neonatal Health: Evidence, Challenges, and Future Directions - Ana Clara Assis Alves Emerick; Letícia Castilho Yamanaka; Stefany Silva Pereira; Tammy Caram Sabatine; Taline de Brito Cavalcante; Thamy Cristina Campos; Gustavo Yano Callado; Edward Araujo Júnior; Antonio Braga; Gloria Calagna; Evelyn Traina (Diagnostics)
Human T-cell lymphotropic virus (HTLV), a retrovirus associated with severe conditions such as leukemia/lymphoma and myelopathy, exhibits variable global prevalence, with higher rates observed in regions such as northeastern Brazil and sub-Saharan Africa. While intrauterine transmission can occur via viral expression in placental tissue and contact with umbilical cord blood, the predominant route is vertical transmission through breastfeeding. Diagnostic testing, particularly serological screening with ELISA and confirmatory methods such as Western blot and PCR, is essential for early detection during pregnancy. The implementation of prenatal screening programs, as seen in Japan and Brazil, has proven effective in reducing vertical transmission by guiding interventions such as breastfeeding cessation in infected mothers. Beyond clinical implications, the psychosocial impact on affected pregnant women highlights the need for an interdisciplinary approach. Although the association between HTLV infection and adverse obstetric outcomes remains controversial, studies suggest increased risks of preterm birth, low birth weight, and other neonatal complications. Given the importance of early diagnosis and prevention, universal prenatal screening protocols represent a critical strategy to reduce viral transmission and its long-term consequences.